EXAMINING THE POLICE OFFICERS’ PHYSICAL AND PERSONAL CHARACTERISTICS BASED ON UNITS - Harmanci, Fatih Mehmet; Caliskan, Aykut; Baycan, Cihangir (European Scientific Journal, ESJ, 2014)
The personality conceptualized as developed personal characteristics and behavior patterns that are to adapt environment and public. Like all occupations, it is important to take into account the duty requirements and personal characteristics while employing personnel to units in the police. In this study, the physical and personal characteristics determined as independent variables and branches of police as a dependent variable. Logistic regression model was applied to reveal the relationships between the variables. The results of study is revealed significantly meaningful relationships between the branches and six personality factors. Among the personal and physical abilities; the emotional stability characteristic causes a negative effect on staffing of branches while extroversion and clarity factors create a positive effect.